The Isothermal Phosphate Adsorption in a New Tidal Rice Field of Barito Kuala Regency South Kalimantan: A Study on Phosphorus Adsorption in Acid Sulfate Soils for Agricultural Improvement - Yusran, Fadly Hairannoor; Mariana, Zuraida Titin; Devita, Windi Bunga (UNIVERSITY OF LAMPUNG, 2025)
High P adsorption reduces rice production, especially in newly reclaimed paddy fields. The research studied soil P adsorption using the adsorption isoterm equation and soil P solubility in a New Tidal Rice Field of Barito Kuala Regency. This incubation study used soil samples from Ray 7, Balandean Village, Alalak District, Barito Kuala Regency, South Kalimantan Province, from May to November 2022. The isothermal adsorption of P was measured in six soil samples with three replicates. P (0, 2, 5, 10, 15, 30, and 50 mg P kg-1) from KH2PO4 were added in 1 g soil in 25 mL 0.01 M CaCl2. The suspensions were shaken at 25 ! for 17 hours, then centrifuged at 3000 rpm for five minutes, and the supernatant was filtered (Whatman 42) for P analysis. Three ordinary adsorption isotherm equations, Langmuir, Freundlich, and Brunauer-Emmett-Teller (BET), were used to fit the data. After adding 50 mg P kg-1, the average dissolved-P was 34.60 mg kg-1 (69%), and adsorbed-P was 15.40 mg kg-1 (31%). The BET equation was more suitable for describing P adsorption isotherm in this type of soil, which has the ability to adsorb one-third of any P addition.